Merkel Cell Carcinoma Masquerading Clinically as a Cyst in a Young Patient - Ashby HE; Jones GN; Leedhanachoke O; Jen P; Helphenstine N; Al Akhrass F (International Medical Case Reports Journal, 2024)
Harty Elouise Ashby,1 Grayson N Jones,1 Oon Leedhanachoke,2 Phillip Jen,3 Noah Helphenstine,3 Fadi Al Akhrass4 1Department of Pathology, Pikeville Medical Center, Pikeville, KY, USA; 2Department of General Surgery, Pikeville Medical Center, Pikeville, KY, USA; 3Department of BioMedical Science, University of Pikeville, Pikeville, KY, USA; 4Department of Infectious Diseases, Pikeville Medical Center, Pikeville, KY, USACorrespondence: Phillip Jen, Department of BioMedical Science, University of Pikeville, 147 Sycamore Street, Pikeville, KY, 41501, USA, Tel +1 704 488 8258, Email phillipjen@upike.eduAbstract: Merkel cell carcinoma (MCC) is an extremely rare and aggressive tumor. Here we report an unusual MCC that manifested as an abruptly enlarging, painful skin lesion over the right antecubital fossa and masqueraded as an epidermal cyst in a 42-year-old male. The lesion was surgically excised and subjected to histopathologic and immunohistochemical examinations. The subsequent analysis allowed for the diagnosis of MCC. Clinicians should always be cognizant of MCC, which can be easily misdiagnosed. Early diagnosis and appropriate treatment are keys to improving the survival rates of MCC patients.Keywords: Merkel cell carcinoma, histopathologic, immunohistochemical, polyomavirus